2022
DOI: 10.1049/cth2.12355
|View full text |Cite
|
Sign up to set email alerts
|

Velocity‐layer Zhang equivalency for time‐varying joint limits avoidance of redundant robot manipulator

Abstract: In the engineering field, a complex system or problem can be transformed into a relatively simple system or problem through equivalency. In this paper, the repetitive motion planning scheme of redundant robot manipulators with time‐varying physical limits are to be optimized via Zhang equivalency (ZE) approach, which includes Zhang equality equivalency (ZEE) approach and Zhang inequality equivalency (ZIE) approach. The ZE approach is presented, theoretically proved, and applied to optimize the control scheme o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…Due to these redundant degrees of freedom, the robotic arm can be more flexibly adapted to different tasks and environments, as well as avoid obstacles or enhance motion performance by adjusting its posture. As a potent tool for real-time parallel processing, neural network models can be used for precise and flexible control of redundant robot manipulators (Xiao and Zhang, 2014;Zhang et al, 2014Zhang et al, , 2018cLiao and Liu, 2015;Jin et al, 2017b;Guo et al, 2018;Tan et al, 2019b;Xiao et al, 2019g;Li et al, 2020dTang et al, 2022;Zhou et al, 2022). More specifically, neural networks can be used in two ways.…”
Section: Related Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to these redundant degrees of freedom, the robotic arm can be more flexibly adapted to different tasks and environments, as well as avoid obstacles or enhance motion performance by adjusting its posture. As a potent tool for real-time parallel processing, neural network models can be used for precise and flexible control of redundant robot manipulators (Xiao and Zhang, 2014;Zhang et al, 2014Zhang et al, , 2018cLiao and Liu, 2015;Jin et al, 2017b;Guo et al, 2018;Tan et al, 2019b;Xiao et al, 2019g;Li et al, 2020dTang et al, 2022;Zhou et al, 2022). More specifically, neural networks can be used in two ways.…”
Section: Related Applicationsmentioning
confidence: 99%
“…This method has been validated on a 4-degree-of-freedom robot manipulator and is found to perform well in solving the redundancy problem of robotic manipulators. Tang et al used an enhanced planning scheme for redundant robot manipulator control (Tang et al, 2022), and a tuning strategy based on this scheme is found to achieve good results in the limit case. Zhang et al propose a differential scheme with varying parameters for the joint-angle drift (J-AD) problem of redundant robot manipulators (Zhang et al, 2018c).…”
Section: Inverse Kinematic Solvingmentioning
confidence: 99%